2022
DOI: 10.1021/acs.jafc.2c08340
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Grafting of 5-Aminolevulinic Acid onto Polylactic Acid Films and Their Photodynamic Potency in Preserving Salmon

Abstract: A novel photodynamic inactivation (PDI)-mediated antimicrobial film of polylactic acid/5-aminolevulinic acid (PLA/ALA) was successfully fabricated by a covalent grafting method using low-temperature plasma. The chemical structure, surface morphology, hydrophilic ability, and mechanical and barrier properties of the films were characterized, and their antibacterial, anti-biofilm potency and preservation effects on ready-to-eat salmon were investigated during storage. Results showed that the amino group of ALA w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…For the modified grafted film, the antibacterial agent is relatively uniformly fixed on the film surface. The cross sections of the five groups of films were relatively uniform and showed no obvious difference, which indicated that plasma treatment and covalently bonded grafting only occurred on the surface, but not inside the film, which was also consistent with the study of Huang and Chen et al 18,33 CS (by covalent fixation) covered the surface of the PLA base film, and the CS layer was observed at the CS-g-PLA base film cross section. The CS layer had an average thickness of 1 μm.…”
Section: Ftir Analysis and Sem Analysissupporting
confidence: 89%
“…For the modified grafted film, the antibacterial agent is relatively uniformly fixed on the film surface. The cross sections of the five groups of films were relatively uniform and showed no obvious difference, which indicated that plasma treatment and covalently bonded grafting only occurred on the surface, but not inside the film, which was also consistent with the study of Huang and Chen et al 18,33 CS (by covalent fixation) covered the surface of the PLA base film, and the CS layer was observed at the CS-g-PLA base film cross section. The CS layer had an average thickness of 1 μm.…”
Section: Ftir Analysis and Sem Analysissupporting
confidence: 89%
“…As a natural intermediary in carbohydrate biosynthesis, the biodegradable and biocompatible polymer PLA splits into monomeric units of lactic acid in the human body . Solvent evaporation, displacement, and diffusion have often been used to create PLA. The salting-out process is characterized by the addition of compounds, such as MgCl 2 and CaCl 2 to separate them into water-miscible and immiscible solvent layers. The principal benefit of salting out is that it reduces the burden on protein capsules …”
Section: Classification Of Biodegradable Polymersmentioning
confidence: 99%
“…Once the films are exposed to light, the PSs will not be artificially controlled and are easily excited and degraded to lose the antibacterial potency. For this consideration, Chen et al (2023) innovatively fabricated a smart PDI-mediated APF by covalently grafting the PS precursor of ALA onto the polylactic acid (PLA) film surface (Figure 7B). The surface of PLA film was immobilized with massive carboxyl groups (-COOH) using the low-temperature plasma.…”
Section: Pdi-mediated Antimicrobial Packaging Filmmentioning
confidence: 99%
“…For this consideration, Chen et al. (2023) innovatively fabricated a smart PDI‐mediated APF by covalently grafting the PS precursor of ALA onto the polylactic acid (PLA) film surface (Figure 7B). The surface of PLA film was immobilized with massive carboxyl groups (‐COOH) using the low‐temperature plasma.…”
Section: Pdi‐mediated Antimicrobial Packaging Filmmentioning
confidence: 99%
See 1 more Smart Citation